Comparison of Functional Outcome between Locking Plate Technique versus Ilizarov Technique in Patients with Complex Tibial Plateau Fractures - Azeem, Muhammad Athar; Ahmed, Ozair Bilal; Manzoor, Behzad; Tahir, Yousaf Bin; Khan, Ghulam Qadir; Majeed, Saqib (Biological and Clinical Sciences Research Journal, 2025)
Complex tibial plateau fractures are challenging to manage because of articular comminution, soft tissue compromise, and the need for early mobilization. Locking plate fixation and hybrid Ilizarov external fixation are commonly used strategies, but comparative evidence on functional outcomes remains limited. Objective: To compare the mean functional knee score between the locking plate technique and the Ilizarov technique in patients with complex tibial plateau fractures. Methods: This randomized controlled trial was conducted in the Department of Orthopedics at Nishtar Hospital, Multan, over 9 months, from 3 August 2024 to 3 April 2025. Adults presenting with complex tibial plateau fractures were enrolled and randomly allocated to Group A (locking plate fixation) or Group B (Ilizarov fixation) using a lottery method with sealed opaque envelopes. All procedures were performed by the same orthopedic surgical team according to institutional protocols, prioritizing meticulous pin tract care and early initiation of knee range of motion. Functional outcome was assessed using the Rasmussen knee score, and radiological union was evaluated on standard follow-up radiographs. Categorical functional outcome was graded as excellent, good, fair, or poor. Continuous variables, including the mean Rasmussen knee score, were compared using an independent-samples t-test. In contrast, categorical variables, such as union status and functional grade, were analyzed using a chi-square test, with p < 0.05 considered statistically significant. Results: Group A demonstrated a significantly higher rate of radiological union than Group B (50.9% vs 17.5%; χ² = 14.1, p < 0.001). The mean Rasmussen knee score was also significantly superior in the locking plate group (25.74 ± 4.52) compared with the Ilizarov group (23.58 ± 3.72, t = 2.78, p = 0.006). Categorical functional outcomes differed significantly between the two groups (χ² = 17.41, p = 0.001), with Group A showing a higher proportion of excellent results (50.9% vs 17.5%) than Group B. Conclusion: Locking plate fixation provides better radiological union and superior functional knee outcomes compared with the hybrid Ilizarov technique in patients with complex tibial plateau fractures, supporting its use as a more reliable and outcome driven option in this clinical setting.